2010
DOI: 10.1523/jneurosci.2067-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

The Spinal Substrate of the Suppression of Action during Action Observation

Abstract: We have previously demonstrated that the forelimb representations of the primary motor and somatosensory cortices, as well as several premotor and parietal areas, are activated by both action-execution and action-observation, indicating that the spectator mentally simulates the observed action. Moreover, several studies demonstrated repeatedly that corticospinal excitability is modulated during action observation, providing evidence of an activation of the observer's motor system. However, evidence for the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…Taken together, these findings would mean that M1 output to spinal interneurons and motoneurons involved in generating movements in hand and digit muscles could be strongly disfacilitated during observation (green bars in Figure 3D). Metabolic activity in monkey spinal cord has been reported to be depressed during action observation [25]; although this could reflect active inhibition, it could presumably also have resulted from a disfacilitation of descending excitation as described here.…”
Section: Resultsmentioning
confidence: 77%
“…Taken together, these findings would mean that M1 output to spinal interneurons and motoneurons involved in generating movements in hand and digit muscles could be strongly disfacilitated during observation (green bars in Figure 3D). Metabolic activity in monkey spinal cord has been reported to be depressed during action observation [25]; although this could reflect active inhibition, it could presumably also have resulted from a disfacilitation of descending excitation as described here.…”
Section: Resultsmentioning
confidence: 77%
“…There must be, in all cases, a way to counter the increment of cortical excitability, as determined by ICF, in order to reduce CSE (Kraskov et al, 2009; Vigneswaran et al, 2013), perhaps involving those circuits responsible for the I-wave (Murakami et al, 2011) or, perhaps, acting at the spinal cord level (Stamos et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…In monkey, inhibition might take place at a spinal level (Stamos et al, 2010), but it is unknown if such a mechanism works in human, as derived from the results of H-reflex studies (Baldissera et al, 2001; Patuzzo et al, 2003; Borroni et al, 2005; Borroni and Baldissera, 2008). A spinal mechanism for suppression of motor replication during movement observation (MO) would fit well with the reported increase in the excitability of the M1 in humans (Fadiga et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of cortico-spinal cells (CST) in areas F5 and M1 display mirror properties (Kilner and Lemon, 2013). Quantitative 2-DG studies have shown reduced bilateral glucose consumption in the cervical segment of the spinal cord during observation of grasping movement (Stamos et al, 2010). These investigators (Evangeliou et al, 2009;Raos et al, 2007) have shown that the action observation/recognition network is, however, much more distributed than originally believed, as to include different sensorimotor areas of both frontal and parietal cortex, thus questioning a unique and crucial role of mirror neurons in other's action and intention understanding, which would instead be dependent on common sensorimotor neurons .…”
Section: The Dorsal Parietal-premotor Stream (Par-d/pmd Cluster)mentioning
confidence: 99%